Ovnen fra Kragelund: Keramik, rekonstruktion og brænding - Hansen, Birgit Als; Sørensen, Morten Aaman; Ørting, Jens Chr. (Hikuin, 2001)
The Kragelund kiln. Reconstruction of a kiln and firing of the pottery By Birgit Als Hansen, Morten Aaman Sørensen and Jens Christian Ørting. The kiln from Kragelund was the largest and most complicated of the three kilns in the experiment. The lower part, with the stoke hole, flues, and the front part of an elevated platform that could safely be copied from the plan of the excavation; whereas the domed roof, its shape and the number of openings and vents partly had to be decided on the basis of experience with previous experiments in kiln building. There were no traces of a wooden structure to support the vault during construction and the dome had to be hand-moulded from several layers of clay. A regular hemispherical form was attempted, with moderate success. A small hole was left open in the top of the dome to let steam out in the early phases of the firing. An opening was made to the rear for stacking the pottery, and later used in a diminished form as a vent to let out exhaust. Another vent in the front of the dome was to allow for regulating the draught during firing. After a couple of firings to dry out the kiln, copies of the original pottery, consisting of glazed jars and pots, were stacked on the platform, and the firing could begin. The next 28 hours gave every opportunity to experiment with adjusting the draught and changing the methods of firing. For a 20-hour period, it seemed impossible to force the temperature up to the desired 900 degrees Celsius. Ultimately, it was decided to try an extensive firing, regardless of the amount of wood consumed. Within a few hours the temperature reached 900-1000 degrees, and the firing was stopped. The stokehole and other openings were blocked up, and to intensify a reduced atmosphere in the kiln, a small mountain of previously removed charcoal was put back into the firing chamber. The experiment could hardly be called a success. The kiln was difficult to manage and consumed far too much wood, and although the pottery was well fired, the glaze was grey and lustreless, with small particles of metallic lead. The sudden rise in temperature in the final phase indicated that intensifying the firing at an early stage could save time and wood, and the lustreless glaze might be caused by the large amount of charcoal, producing an atmosphere excessively deficient in oxygen.